Sinfonie no. 5 in C mol op. 67 von Louis van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Ganz, Adolf,:::::::::; d 1795-1869:::Contributor::::::::::::; Breitkopf & Härtel:::Contributor:::::::::::: (Leipzig; Germany, 2022)
Manuscript score of Beethoven's Fifth Symphony in the hands of two different copyists, with title leaf in the hand of Adolf Ganz, prepared for Breitkopf & Härtel's lending library in Leipzig ("in der Leihbibliothek No. 3442" inscribed on title page), likely copied from the second impression of the first edition of the parts published in 1809. Contains handwritten notes by Mr. Bachmann in pencil regarding textual variances between this score and Beethoven's autograph, as well as the first printed editions; a few corrections are written in a unidentified hand in crayon. Bound in a stiff paper cover with marbled paper covering and handwritten label.